2018
DOI: 10.1155/2018/1708650
|View full text |Cite
|
Sign up to set email alerts
|

Is a Combination of a GnRH Agonist and Recombinant Growth Hormone an Effective Treatment to Increase the Final Adult Height of Girls with Precocious or Early Puberty?

Abstract: The aim of treatment for idiopathic central precocious puberty (ICPP) is to increase final adult stature, for which gonadotropin-releasing hormone agonist (GnRHa) is the gold standard. Early puberty is frequently similar to ICPP, with pubertal onset only slightly advanced. Short stature may result from early pubertal onset. Some studies have suggested that recombinant human growth hormone (rhGH) should be combined with a GnRHa to improve adult height, while others have not. Here, the aim was to compare the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[491718] Song et al in a meta-analysis from five studies of EP girls concluded that combination therapy could not significantly differ between final adult height SDS and initial height SDS in treated EP girls. Although individual reports suggest the beneficial effects of combined therapy on improving adult height[5] again, the controversies of view exist between experts in this field toward combined therapy, especially when the cost of drugs is too high. There is a report from China on GnRHa and rhGH in combination or GnRHa alone on the treatment of EP girls which argue that PAH at the end of combined therapy was higher than GnRHa alone, although the different was insignificant and both treatments had a similar effect on the final height of EP girls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[491718] Song et al in a meta-analysis from five studies of EP girls concluded that combination therapy could not significantly differ between final adult height SDS and initial height SDS in treated EP girls. Although individual reports suggest the beneficial effects of combined therapy on improving adult height[5] again, the controversies of view exist between experts in this field toward combined therapy, especially when the cost of drugs is too high. There is a report from China on GnRHa and rhGH in combination or GnRHa alone on the treatment of EP girls which argue that PAH at the end of combined therapy was higher than GnRHa alone, although the different was insignificant and both treatments had a similar effect on the final height of EP girls.…”
Section: Discussionmentioning
confidence: 99%
“…Early puberty (EP) is due to the activation of GnRH pulse generator in lower ages, occurring often in girls;[5] EP may be a potential cause for impairment of adult height. In EP girls, the pubertal onset is slightly advanced, leading to a short stature which may impose psychological problem both in children and parents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data extracted included the rst author, year of publication, country where the study was conducted, number of participants, number of patients lost to follow-up, mean age of participants, diabetes duration, intervention duration, clinical outcomes, and safety outcomes. Studies were excluded if they were case reports, letters, comments, or editorials or if no quantitative outcomes were reported 15 . The primary clinical outcomes of interest were cIMT 9 , reactive hyperemia index (RHI) 16 , ow-mediated dilation (FMD) 17 , pulse wave velocity (PWV) 18 , wall shear stress (WSS) 19 , and glucose infusion rate/insulin (M/I) 20 .…”
Section: Data Extractionmentioning
confidence: 99%